RETRACTED ARTICLE: Analysis on energy consumption in smart grid WSN using path operator calculus centrality based HSA-PSO algorithm - Hemalatha, R.; Prakash, R.; Sivapragash, C. (Soft computing (Berlin, Germany), 2020)
In this paper, the consumption of energy is efficiently balanced using the high searching capability of harmony search algorithm (HSA). However, centrality in finding the route is considered as an utmost challenge in finding the important node in WSN. Hence, the path operator calculus centrality (SPOCC) is used to optimize the centrality problems in routing. The SPOCC finds the main routing path using HSA, and high centrality node is estimated by particle swarm optimization (PSO) algorithm, thereby ensuring optimal routing with reduced energy consumption. The utilization of PSO improves the lifetime of nodes using its dynamic capability. The performance of the proposed hybrid algorithm is evaluated using the various result metrics in smart grid outdoor transmission environment. The results show that the proposed hybrid algorithm obtains better improvement in terms of reduced delay and high residual energy than the existing algorithms.